The role of the structural funds and cohesion fund in the stimulation of sustained economic growth in Poland - Jacek Szlachta (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Having joint the European Union, Poland, as one of the poorest member state, hopes for a significant financial support. Indeed the policy of catching up of less developed regions of the UE seems to be important element of the integration process. In addition to the cohesion fund, Poland can benefit from the four structural funds. It is estimated that in the years 2007-2011 Poland might be able to receive as much as 63 billion euro, out of which 54 billion may account to the cohesion policy.
Keywords: 330; Wirtschaftswachstum; EU-Strukturfonds; EU-Strukturfonds; Polen